LIXIVIACION DE LA DOLOMITA Y LA OBTENCION DE UN FERTILIZANTE LIQUIDO DE ACETATO DE CALCIO DE LA MINA “DON RICARDO” OCUCAJE ICA - CÁRDENAS RODRÍGUEZ, FLORENTINO GALO (2016)
For the innovation of a liquid calcium fertilizer, dolomite was used and it was prepared at -200M to be processed by leaching with acetic acid, obtaining the product of calcium acetate in the condition of liquid fertilizer, the variables related to the process were manipulated As the Ph, temperature granulometry concentration of salts in the suspension, the data obtained was processed in order to obtain mathematical models to simulate the process, in the simulation it was possible to define the optimum point of obtaining in time and as a function of pH.